Calcium phosphate product level as a predictor for arteriovenous fistula re-operations in patients with chronic renal failure. (June 2019) - Tüysüz, Mehmet Erin; Dedemoğlu, Mehmet
Objectives: There is an increased calcium phosphate product level causing the formation of calcification in the arterial wall and thus decreased quality of fistula in patients with chronic renal failure. The purpose of our study is to verify the relationship between arteriovenous fistula re-operation and high calcium phosphate product level. Methods: Seventy-nine consecutive patients with chronic renal failure between April 2016 and February 2018 were included in the study. Patients having calcium phosphate product level ≥50 mg 2 /dl 2 were defined as group 1, whereas those having <50 mg 2 /dl 2 were defined as group 2. Primary outcome of interest was the need for re-operation during the follow-up and to determine the risk factors for re-operation. To determine independent predictors for re-operation, multivariate logistic regression model was used. Results: The rates of redo and tredo operation were significantly higher in group 1 compared to group 2 ( p = 0.01 and 0.04). In multivariate analysis, phosphate (OR: 1.84, 95% CI: 1.00–3.40, p = 0.05) and triglyceride (OR: 1.01, 95% CI: 1.00–1.02, p = 0.04) levels for redo operation and calcium phosphate product level (OR: 1.11, 95% CI: 1.01–1.22, p = 0.03) for tredo operation were found to be independent predictors. Conclusions: High calcium phosphate product level leads to increased risk of arteriovenous fistula re-operation by causing arterial stiffness in this patient group. Additionally, these re-operations place additional burden on morbidity and cost efficacy. Thus, we recommend keeping the calcium phosphate product level at the optimal level in these patients to avoid both the risk of arteriovenous fistula re-operation and the other cardiovascular problems.